Student Affairs Program Management Analysis Pattimura University - Pattiruhu, French O.; Matakupan, Anthoneta; Toisuta, Divy A.; Taihuttu, Elvenda Ch. A. (ProBisnis : Jurnal Manajemen, 2025)
Performance management in all areas, including the student affairs sector at Pattimura University, has a significant influence on the achievement of planned work targets in the field. The performance of an employee becomes a barometer in achieving the results of the implementation of the program set by the institution/institution/organization and the implementing work unit. And therefore the arrangement described in the main tasks and functions of the Student Affairs and Public Relations section which provides services for fostering student interests, talents, and welfare, managing data and facilitating alumni activities and public relations affairs is expected to run well in accordance with applicable provisions. Research on the Analysis of Student Affairs Program Management is intended to understand the appropriate strategy model that can be used for the development of student affairs and contribute to the future development of the university, and can provide significant benefits to the direction of policy in this field. The implementation of the right strategy must be accompanied byevaluation, analysis and identification of various factors that are weaknesses so that performance achievements can be measured and sustainable.